Relevance of Structural Brain Connectivity to Learning and Recovery from Stroke - Johansen-berg, Heidi; Scholz, Jan; Stagg, Charlotte J. (Frontiers in Systems Neuroscience, 2010)
The physical structure of white matter fibre bundles constrains their function. Any behaviour that relies on transmission of signals along a particular pathway will therefore be influenced by the structural condition of that pathway. Diffusion-weighted magnetic resonance imaging provides localised measures that are sensitive to white matter microstructure. In this review, we discuss imaging evidence on the relevance of white matter microstructure to behaviour. We focus in particular on motor behaviour and learning in healthy individuals and in individuals who have suffered a stroke. We provide examples of ways in which imaging measures of structural brain connectivity can inform our study of motor behaviour and effects of motor training in three different domains: (1) to assess network degeneration with healthy ageing and following stroke, (2) to identify a structural basis for individual differences in behavioural responses and (3) to test for dynamic changes in structural connectivity with learning or recovery.